2009
DOI: 10.1037/a0016213
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relations of children’s effortful control, impulsivity, and negative emotionality to their externalizing, internalizing, and co-occurring behavior problems.

Abstract: The purpose of the study was to examine the relations of effortful control (EC), impulsivity, and negative emotionality to at least borderline clinical levels of symptoms and change in maladjustment over four years. Children's (N = 214; 77% European American; M age = 73 months) externalizing and internalizing symptoms were rated by parents and teachers at 3 times, 2 years apart (T1, T2, and T3) and were related to children's adult-rated EC, impulsivity, and emotion. In addition, the authors found patterns of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
497
5
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 570 publications
(581 citation statements)
references
References 97 publications
56
497
5
12
Order By: Relevance
“…Contrary to our Hypotheses 1b and 3b, children's negative emotionality was not found to be uniquely related to their task avoidance or anxiety. Previously, negative emotionality has been found to be associated, for example, with elementary school students' state anxiety (e.g., Eisenberg et al, 2009;Nelson et al, 1999). In the present study, negative emotionality did show a significant bivariate correlation with active task avoidance, although it was not a significant predictor for task avoidance when the impacts of other temperamental characteristics were taken into account.…”
Section: Temperament Affects and Behaviors 18contrasting
confidence: 50%
See 2 more Smart Citations
“…Contrary to our Hypotheses 1b and 3b, children's negative emotionality was not found to be uniquely related to their task avoidance or anxiety. Previously, negative emotionality has been found to be associated, for example, with elementary school students' state anxiety (e.g., Eisenberg et al, 2009;Nelson et al, 1999). In the present study, negative emotionality did show a significant bivariate correlation with active task avoidance, although it was not a significant predictor for task avoidance when the impacts of other temperamental characteristics were taken into account.…”
Section: Temperament Affects and Behaviors 18contrasting
confidence: 50%
“…Temperament has been examined in relation to, for example, students' achievement, student-teacher interactions, problem behavior, and psychosocial functioning at school (e.g., Eisenberg et al, 2009;Nelson, Martin, Hodge, Havill, & Kamphaus, 1999;Valiente, Lemery-Chalfant, & Swanson, 2010;Zhou, Main, & Wang, 2010). For example, studies among kindergartners and elementary school students have found good self-regulation or high effortful control to be positively related to students' self-efficacy (Liew, McTigue, Barrois, & Hughes, 2008), academic competence (Liew et al, 2008;Valiente et al, 2010;Zhou et al, 2010), classroom participation (Valiente, Lemery-Chalfant, Swanson, & Reiser, 2008), school liking (Valiente, Lemery-Chalfant, & Castro, 2007), and work habits (Curby, Rudasill, Edwards, & Pérez-Edgar, 2011).…”
Section: Temperament In the School Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, the link between NE and later problematic behaviour and psychopathology has been well established (e.g., Eisenberg et al, 2009). The moderating role of NE in treatment outcome aimed at improving internalizing and externalizing behaviour (Blair, Mitchell, & Blair, 2005) suggests that targeting contributing factors of NE could be effective in preventing the development of childhood psychopathology.…”
Section: Summary and Implicationsmentioning
confidence: 95%
“…NE is associated with the development of later problematic behaviour and psychopathology (Eisenberg et al, 2009;Fox, Henderson, Rubin, Calkins, & Schmidt, 2001;Hyde, Mezulis, & Abramson, 2008). For example, fearful temperament is associated with childhood anxiety disorders (Degnan, Alma, & Fox, 2010;Goldsmith & Lemery, 2000), while NE is associated with depression (Phillips, Lonigan, & Driscoll, 2002) and maladjustment (Eisenberg et al, 2009). Understanding early influences of NE on socio-emotional development (Davis, Glynn, Schetter, Hobel, Chicz-demet, & Sandman, 2007;Davis, Snidman, Glynn, Dunkel Schetter, & Sandman, 2004;Hayden et al, 2010;Hayden et al, 2007) could inform efforts at prevention and early intervention.…”
mentioning
confidence: 99%